Research on control algorithm of a four axis air vehicle-inverted pendulum system - Fanguo KONG; Zhaoxing LI; Jiancun ZHANG; Gang XIONG; R.Nyberg Timo (智能科学与技术学报)
Controlling the balance of a movable rod or a wine cup filled with water on a four axis air vehicle is a hard job.A system called four axis air vehicle-inverted pendulum balance control system is needed.With this special kind of balance control system and the idea of a simplified model to replace the complex system for analysis,the performance of a linear four axis vehicle-inverted pendulum on X-Z plane was studied,its dynamic and physical formula was also discussed.The simplified model equipped with the control algorithm of sliding mode control was designed and simulated on the computer with the help of MATLAB.The result shows that the control algorithm works well on the four axis air vehicle-inverted pendulum balance control system and the system has a good performance.